Fashion and death: Trends Cycles (ModaPalavra e-periódico, 2017)
Fashion is composed of cycles subpostostrends that seek to eliminate the past for a new one, which makes it ephemeral and eternal at the same time. This study investigates how is the relationship between these cycles of trends over time, through a brief history of fashion, considering the theoretical rules of Simmel, Crane and Caldas. They will still be used concepts proposed by Agamben, such as: device, in order to classify the system of the fashion; contemporaneidade, to understand the action of that factor in relation to the time and profanation, to identify the capacity to maintain in the society. It is ended that the fashion, as well as the death, renews the society, it destroys and it creates the new, as a system naturalized artificially.
Keywords: fashion; profanation; cycle